Synaptic and Network Contributions to Anoxic Depolarization in Mouse Hippocampal Slices. (1st May 2021) - Heit, Bradley S.; Dykas, Patricia; Chu, Alex; Sane, Abhay; Larson, John
Highlights: Time between anoxic depolarization (AD) and re-oxygenation dictates degree of electrophysiological recovery after anoxia. Adenosine A1 receptor antagonism has no effect on AD latency or the potential for recovery. Antagonism of AMPA- and NMDA-receptors prolongs AD latency and flattens AD waves. AD latency is longer in CA1 when disconnected from CA3. AD latency in CA1 is protracted in female mice compared to male mice. Abstract: Ischemic stroke remains the third leading cause of death and leading cause of adult disability worldwide. A key event in the pathophysiology of stroke is the anoxic depolarization (AD) of neurons in the ischemic core. Previous studies have established that both the latency to AD and the time spent in AD prior to re-oxygenation are predictors of neuronal death. The present studies used hippocampal slices from male and female mice to investigate the electrophysiological events that affect latency to AD after oxygen deprivation. The results confirm that the epoch between AD and re-oxygenation largely determines the magnitude of synaptic recovery after anoxic challenge. Using a selective antagonist of adenosine A1 receptors, we also confirmed that adenosine released during anoxia (ANOX) suppresses synaptic glutamate release; however, this action has no effect on AD latency or the potential for post-anoxic recovery of synaptic transmission. In contrast, antagonism of AMPA- and NMDA-type glutamate receptors significantly prolongs the latency to AD and alters the speed and synchrony of associated depolarizing waves. Experiments using slices with fields Cornu ammonis 3 (CA3) and Cornu ammonis 1 (CA1) disconnected showed that AD latency is longer in CA1 than in CA3; however, the early AD in CA3 is propagated to CA1 in intact slices. Finally, AD latency in CA1 was found to be longer in slices from female mice than in those from age-matched male mice. The results have implications for stroke prevention and for understanding brain adaptations in hypoxia-tolerant animals.